2021
DOI: 10.2196/31185
|View full text |Cite
|
Sign up to set email alerts
|

A Technology-Based Training Tool for a Health Promotion and Sex Education Program for Justice-Involved Youth: Development and Usability Study

Abstract: Background Justice-involved youth are especially vulnerable to mental health distress, substance misuse, and risky sexual activity, amplifying the need for evidence-based programs (EBPs). Yet, uptake of EBPs in the justice system is challenging because staff training is costly in time and effort. Hence, justice-involved youth experience increasing health disparities despite the availability of EBPs. Objective To counter these challenges, this study deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Namely, youth delinquency and court-involvement cause stress and strain on the family system, and the family unit itself impacts youth behavior with notable potential for buffering and improvement in outcomes. Viewing delinquency in the context of both psychopathology and family factors is consistent with the Social-Personal Framework (SPF), which has been previously utilized in interventions targeting adolescent risk behaviors (Donnenberg et al, 2018;Brown et al, 2014;Snow-Hill et al, 2021;Kendall et al, 2017). The SPF highlights that adolescent risk-taking does not occur in isolation, but rather in the setting of personal attributes, family context, peer and partner relationships, and environmental circumstances (Donenberg & Pao, 2005).…”
Section: Introductionsupporting
confidence: 54%
“…Namely, youth delinquency and court-involvement cause stress and strain on the family system, and the family unit itself impacts youth behavior with notable potential for buffering and improvement in outcomes. Viewing delinquency in the context of both psychopathology and family factors is consistent with the Social-Personal Framework (SPF), which has been previously utilized in interventions targeting adolescent risk behaviors (Donnenberg et al, 2018;Brown et al, 2014;Snow-Hill et al, 2021;Kendall et al, 2017). The SPF highlights that adolescent risk-taking does not occur in isolation, but rather in the setting of personal attributes, family context, peer and partner relationships, and environmental circumstances (Donenberg & Pao, 2005).…”
Section: Introductionsupporting
confidence: 54%
“…In the United States, SRH telehealth interventions were found to increase self-efficacy with condom use [ 2 ] and were found feasible for screening for sexually transmitted infections [ 3 ]. With a focus on subgroups of adolescents, mHealth interventions targeted homeless adolescents [ 4 ], trans youth [ 5 , 6 , 7 ], and justice-involved youth [ 8 ]. This underscored the importance of mHealth interventions because numerous homeless and LGBTQ+ youth own a mobile phone, and many reported mental health issues, substance abuse, eating disorders, homelessness, risky sexual behaviors, and victimization during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Justice-involved youth were especially vulnerable to risky sexual behaviors and mental health issues during the pandemic. Snow-hill et al [ 8 ] tested and adapted the PHAT-Life intervention with juvenile justice staff and found that this intervention could be sustained within the justice system setting.…”
Section: Introductionmentioning
confidence: 99%